2019
DOI: 10.1590/1807-7692bar2019180103
|View full text |Cite
|
Sign up to set email alerts
|

Gamification in Management Education: A Systematic Literature Review

Abstract: Quality of teaching is increasingly important for the success of educational institutions. In this context, gamification is a tool often used to improve the teaching-learning process by helping both teachers and students reach their goals in the short, medium and long term. Given the importance of the topic both in academia and society, this article presents a systematic review of the literature on the use of gamification as a tool to enhance the quality of the teaching process in general, and, in particular, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 181 publications
1
26
0
3
Order By: Relevance
“…In addition, the self-efficacy of an instructor is an important factor. High self-efficacy will encourage users to use the gamified system and vice versa (Adukaite et al 2017 ; da Silva et al 2019 ; Huang and Ren 2020 ; Susanto et al 2017 ). Table 1 shows a summary of the literature pertaining to the adoption of gamified systems in banking, learning, sport, and exercise.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the self-efficacy of an instructor is an important factor. High self-efficacy will encourage users to use the gamified system and vice versa (Adukaite et al 2017 ; da Silva et al 2019 ; Huang and Ren 2020 ; Susanto et al 2017 ). Table 1 shows a summary of the literature pertaining to the adoption of gamified systems in banking, learning, sport, and exercise.…”
Section: Literature Reviewmentioning
confidence: 99%
“…SE was found also to be an essential factor for using the gamified system (Adukaite et al 2017 ; Susanto et al 2017 ). A review study found that SE is a driving variable of gamification (da Silva et al 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For more information about GBL see Pivec 2007;Garris et al 2002. For gamification, see Kapp 2012Marczewski 2015;Werbach, Hunter 2015, and the review of literature of Kasurinen, Knutas 2018;Ardila-Muñoz 2019;Silva et al 2019. 13 Garibaldi, Garibaldi 2017 14 About the problems that teachers have among education students about time conception and how to teach it and the use of chronologies see Santiesteban 2007 and Pages, Santiesteban 2010.…”
Section: Playing and Learning With Chronologies: The Use Of Timeline In The University Classroommentioning
confidence: 99%
“…De acordo com[13], a gamificação pode ser agrupada em quatro conceitos principais que explicam como aplicá-la no contexto educacional, são eles: Motivação (Motivation), Atitudes (Attitudes), Fluxo (Flow) e Aprendizagem (Learning).Cada um desses conceitos podem ser explorados de forma dinâmica e personalizada, atendendo às peculiaridades da escola e/ou do público-alvo.…”
unclassified